The Role of Interactive Technology in Retail Design: A Case Study Within the Fashion Sector - Wang, Mian; Marsden, Jamie; Oguz, Ezgi; Thomas, Briony (Journal of Marketing Development and Competitiveness, 2023)
This paper explores the role of interactive technology in retail design, and the prerequisites of the designed retail environment in optimizing customer experience and brand experience. Adopting a case study method, primary data was obtained using semi-structured interviews with 20 experts directly involved in the three chosen cases. The research contributes to the lack of extensive literature on interactive technology in physical retail, specifically within the fashion field. By connecting three topics of academic research – physical retail environment, the role of interactive technology and in-store customer experience and brand experience – it suggests the prerequisites for designed retail environments in optimizing customer experience and brand experience.